Perlunya Reformasi Kultural di Kepolisian Republik Indonesia - Ahmad Fityan Abdussalam; Hamidah Abdurrachman; Achmad Irwan Hamzani (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
The purpose of this study is the need for cultural reforms to be carried out in the Indonesian National Police (Polri), efforts to reform police culture in the grand design road map for reform of the police bureaucracy, examines policy efforts to revitalize Polri's human resources and the obstacles associated with the Inspector General FS case. This type of research includes library research. While the approach used is a normative approach. This study uses secondary data obtained from laws and regulations, books and scientific journals. The results of this study indicate that the police reform policy in the cultural aspect associated with bureaucratic reform includes: changes in doctrine and main guidelines, formulation of behavioral guidelines; and empowerment of non-commissioned officers and enlisted police officers in Community Police (Polmas) efforts; Quick wins program and revitalization of Polri's human resources. Polri needs to re-inculcate and re-orient the guidelines and principles established by the police both in the education and care of every member of the Polri and for Polri to take concrete steps by creating special instruments other than a code of ethics that regulates the corps mental conduct so that actions